Transition-Metal Free Chemoselective C(sp3)-S Cross-Coupling/Cyclization Cascade: Reagent-Controlled Divergent Synthesis of Methylene-Functionalized Thiazolidines and 1,3-Thiazinanes - Kumar, Vipin; Yadav, Anup Kumar; Singh, Saurabh; Singh, Maya Shankar (Synlett)
A highly chemoselective consecutive cross-coupling/cyclization cascade of β-ketothioamides with dihaloalkanes has been achieved under transition-metal free condition, enabling the formation of methylene-functionalized thiazolidines and 1,3-thiazinanes at room temperature in open air in high yields. The typical features of this straightforward sustainable approach include readily accessible starting materials, simple one-pot operation, atom-/step-economy, cost-effective, good substrate scope, and scalability. Noteworthy, HX is the only by-product, and stereochemistry of the exocyclic methylene moiety was assigned to have Z-configuration. Late-stage functionalization could provide new opportunities for the discovery of N, S-heterocyclic drugs, and other potential functional molecules.